2007
DOI: 10.1080/10256010701550732
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer nitrogen isotope signatures

Abstract: There has been considerable recent interest in the potential application of nitrogen isotope analysis in discriminating between organically and conventionally grown crops. A prerequisite of this approach is that there is a difference in the nitrogen isotope compositions of the fertilizers used in organic and conventional agriculture. We report new measurements of delta15N values for synthetic nitrogen fertilizers and present a compilation of the new data with existing literature nitrogen isotope data. Nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
253
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(266 citation statements)
references
References 25 publications
11
253
2
Order By: Relevance
“…Grazers may intensify losses of 15 N-depleted products from soils, thereby leading to further increase in soil δ 15 N (Frank and Evans, 1997). Mineral N fertilizers have been reported to have low δ 15 N values, ranging from at −1.4 to 2.6‰ in NH 4 NO 3 and −5.9 to −0.8‰ in urea (Bateman and Kelly, 2007). Accordingly, δ 15 N values decreased during spring and summer when fertilizers were applied (Fig.…”
Section: Changes In Natural Abundance Of 13 C and 15 Nmentioning
confidence: 99%
“…Grazers may intensify losses of 15 N-depleted products from soils, thereby leading to further increase in soil δ 15 N (Frank and Evans, 1997). Mineral N fertilizers have been reported to have low δ 15 N values, ranging from at −1.4 to 2.6‰ in NH 4 NO 3 and −5.9 to −0.8‰ in urea (Bateman and Kelly, 2007). Accordingly, δ 15 N values decreased during spring and summer when fertilizers were applied (Fig.…”
Section: Changes In Natural Abundance Of 13 C and 15 Nmentioning
confidence: 99%
“…The method has a d 18 O precision To test the hypothesis that urea deicers were the source of NO 3 À in the Main Lake depression water, a sample of commercial urea was analyzed, yielding a d 15 N value of À1.0 AE 0.23% (n = 9). Most synthetic N compounds have d 15 N close to zero because they are synthesized by H 2 reduction of atmospheric N 2 (0%) at high temperature (Haber-Bosch process), with negligible isotopic fractionation during the production process [24]. The large difference between the d 15 N values of the urea and the Main Lake depression NO 3 À suggests that the Main Lake depression NO 3 À was not derived from urea deicers.…”
Section: Methodsmentioning
confidence: 99%
“…The δ 15 N of synthetic fertilizer is generally lower than that of organic fertilizer, and the mean δ 15 N is -0.2‰ for synthetic fertilizer, 8.1‰ for manure/compost, 2.5‰ for seaweed-based, 5.9‰ for non-manure wastes of livestock, and 7.1‰ for fishbased materials (Bateman and Kelly, 2007). The current researches have showed that crops grown with synthetic fertilizer tend to have consistently lower δ 15 N (0-5‰) than those with non-synthetic fertilizer (3‰-15‰) if other conditions are the same (Chang and Choi, 2009).…”
Section: Nitrogen Source Identification Of Ecosystemmentioning
confidence: 99%